[Article about results of fight attendant smoking survey) (Tufts Archival Research Center, 2007)
Marginalia; Article summarizing a survey of flight attendants regarding personal health in relation to smoking and smoking on flights. Iterates that Representatives are working on the fight for a total ban on in-flight smoking, despite Elizabeth Dole's statement that more research was needed. Lists side stream effects and respiratory ailments of flight attendants, as well as cigarette related fire or potential fire causes.